Costa Rica 2025 - Brooklyn, Cassandra (Travel writer); Ferrarese, Marco, 1980-; Gilbert, Sarah (Travel writer); Jimenez, Christa; Kaminski, Anna; Lavis, Elizabeth; Paska, Marisa (Lonely Planet guidebooks., 2025)
Discover Costa Rica's most popular experiences and best kept secrets from catching a glimpse of shy sloths and white-faced monkeys in Parque Nacional Manuel Antonio; to marvelling at the five scenic cascades in the Central Valley's La Paz Waterfall Gardens; and taking an educational bean-to-bar cacao tour at an organic farm in Rio Celeste.